Characterization of the Chemical Components of Various Onion Species in West Sumatra - Fenita Miati; Fauzan Azima; Daimon Syukri (Green Engineering Society, 2025)
Various types of onions have long been utilized as both culinary ingredients and traditional medications, yet comprehensive comparative data on their chemical composition and antioxidant potential in Indonesia are limited. This study provides the first integrated analysis of six onion species cultivated in West Sumatra, namely, shallot (A. cepa var. ascalonicum), garlic (A. sativum), common onion (A. cepa L.), Dayak onion (Eleutherine palmifolia), chive (A. tuberosum), and leek (A. fistulosum L.). Physicochemical properties were determined through proximate analysis, antioxidant activity was assessed using the DPPH assay and expressed as IC₅₀ values, and lipid-based phytochemical profiles were obtained via Bligh and Dryer extraction, followed by GC–MS. Data were processed and visualized in RStudio. The results indicate that chive exhibited the highest moisture (93.57%) and fat (4.15%) contents, whereas Dayak onion contained the highest amounts of ash (6.29%) and protein (8.74%). Dayak onion exhibited strong antioxidant activity (84.85 ppm), whereas common onion, shallot, and leek demonstrated weak antioxidant activity. Cis-vaccenic acid was the dominant compound in shallot (37.59%) and leek (31.19%), and D-limonene was the dominant compound in Dayak onion (22.39%) and chive (21.16%). The study findings highlight that the Dayak onion is a promising indigenous source of natural antioxidant for functional food and herbal product development, while providing novel baseline phytochemical data for advancing onion bioactivity and biodiversity research.